1992
DOI: 10.1093/oxfordjournals.jbchem.a123789
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Cis-Elements Regulating the Rat AMOG (Adhesion Molecule on Glia)/Na,K-ATPase β2 Subunit Gene1

Abstract: We have identified a positive regulatory cis-acting element of the adhesion molecule on glia (AMOG)/Na,K-ATPase beta 2 subunit gene as GAGGCGGGG at position -87 to -79 by transient transfection assay using B103 cells (rat neuroblastoma cell line). The newly identified AMOG regulatory element (AMRE) enhanced the promoter activity in a mutually compensating manner with the Sp1 element at position -147 to -142. AMRE acts as a positive regulatory element not only in B103 cells but also in 3Y1 (rat embryo cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sequence analysis revealed a potential TATA box (−29 bp); two Sp1 binding sites (−55 and −147 bp) and a serum response element (SRE: −263 bp) on the rat Atp1b2 promoter region (Kawakami et al, 1990 ). In addition, an AMOG regulatory element (AMRE: GAGGCGGGG at position −87 to −79 bp) and a functional Sp1 binding site (−147 to −142 bp) were found in rat Atp1b2 promoter regions (Kawakami et al, 1992 , 1993 ).…”
Section: Promoter Analysis Of Nak-atpase α- and β-Subunitsmentioning
confidence: 99%
“…Sequence analysis revealed a potential TATA box (−29 bp); two Sp1 binding sites (−55 and −147 bp) and a serum response element (SRE: −263 bp) on the rat Atp1b2 promoter region (Kawakami et al, 1990 ). In addition, an AMOG regulatory element (AMRE: GAGGCGGGG at position −87 to −79 bp) and a functional Sp1 binding site (−147 to −142 bp) were found in rat Atp1b2 promoter regions (Kawakami et al, 1992 , 1993 ).…”
Section: Promoter Analysis Of Nak-atpase α- and β-Subunitsmentioning
confidence: 99%
“…To reveal the molecular mechanisms of the tissue-specific, developmental, and hormonal regulation of Na,K-ATPase gene expression and of the coordinated regulation between the a-and 13-subunit genes, we have performed a systematic analysis of the genes encoding a-and 13-subunit isoforms, including their 5'-flanking regions where important regulatory functions reside (15,17,18,43). We cloned from the rat chromosome a 13.3-kb DNA fragment that included the Na,K-ATPase al subunit gene (ATPlA1) and 5' flanking region (EMBL/GenBank data library accession number X51461), and identified the transcription initiation site at 262 bp upstream from the translation initiation codon (43).…”
mentioning
confidence: 99%
“…CAT activity was assayed as described previously (10,17). The acetylated chloramphenicol was separated by thin-layer chromatography and analyzed by a radioanalytic imaging system (AMBIS System, Inc., San Diego, Calif.).…”
mentioning
confidence: 99%
“…The transcription factor specificity protein 1 (Sp1) binds GC-rich motifs and regulates gene expression through protein–protein interactions (Shull et al, 1989 ; Samson and Wong, 2002 ). Based on previous works by Kawakami et al ( 1990 , 1992 ) and Avila et al ( 1998 ) that reported that Sp1 enhances the promoter activity of the β 2 subunit in rat neuroblastoma, in rat embryo cell lines and in human lymphocytes, we suspected that Sp1 could be at least one of the factors regulating this process. Therefore, we explored whether Sp1 was involved in the up-regulation of the β 2 subunit during the re-morphogenesis of ARPE-19 cells.…”
Section: Resultsmentioning
confidence: 91%